Pengaruh Media Balok Bergambar Dalam Meningkatkan Kemampuan Pengurangan Bagi Anak Berkesulitan Belajar - Yulia Fitri; Zulmiyetri Zulmiyetri (Jurnal Penelitian Pendidikan Khusus, 2018)
The background this research was, the child who cant on learning disabilities in forth is because the child has not been able to solve the reduction operations of multiplication correctly. Children may not be able to complete with  dozen multiplication aritmatch operations with learning disabilities using balokbergambar technique in match. Research methods are implemented through single subject research data with use design A-B-A. The ability of children multiplication through a written test. Technique is used VisuaAnalisis of Grafik Data). The result are analyzed include the number of observation in the baseline (A-1) four time, in condition intervensiion (B) eigh time. In the condition in baseline (A-2) two time.The result showed that the balokbergambar technique can improve the ability of children multiplication aritmatch operation significantly.